TIDAL HARMONIC ANALYSIS AND PREDICTION TO SUPPORT EARLY WARNING FOR COASTAL FLOODING - Firdaus, Randi; Tazaroh, Nurul; Surendra, Oky; Prasetyo, Eko; Adriyanto, Riris (BULLETIN OF THE MARINE GEOLOGY, 2024)
The Indonesian Maritime Continent (IMC) is the largest archipelago that vulnerable to climate change especially sea level rise. Some coastal areas frequently experience coastal flooding affecting the activities and infrastructures. Thus, an accurate tide prediction in this region plays a pivotal role in providing the early warning, mitigation, and adaptation to frequent coastal flooding. BMKG, through the Center for Marine Meteorology has done undertaken efforts to provide an accurate tidal prediction information by developing the tidal information system call the Indonesian Tidal Information System (INATIS). Tidal harmonic analysis (THA) using the least-square method was applied to sea level data from 49 Marine Automatic Weather System (MAWS) stations collected between 2020-2021 to generate tidal predictions for the period of 2022-2023. Accuracy was assessed based on Mean Absolute Error (MAE) and the Mean Absolute Percentage Error (MAPE). MAWS stations with prediction accuracy above 80% visualized on publicly accessible online platform of the BMKG website using the open-source Looker Studio. Verification of the tidal predictions showed an average prediction accuracy of 93.21% with a MAE of 0.11 m. The high accuracy of INATIS demonstrates its potential as a reference for coastal flood early warning systems.